Apuntes sobre aves colombianas (1958)
This work includes miscellaneous notes on ten species of colombian birds. Three new subspecies are described, they are Thamnophilus multistriatus oecotonophilus, Campylorhynchus griseus zimmeri and Campylorhynchus zonatus imparilis. Basileuterus xantnophrys is redescribed, and Cyanocorax sclateri is accepted as a valid subspecies of C. affinis; also some descriptive or critical notes are given, including the description of some plumages and notes on extension of the range of one of the least known parrotlets, Touit stictoptera stictoptera, previously recorded only from Fusagasugá. near Bogotá, and by "Bogotá" trade-skins.